Energy potential, health benefits, antinutrient reduction methods, and nutritional properties of Indian millets: a review - Gatkal, N. R.; Shelke, M. S.; Nalawade, S. M.; Deshmukh, M. S.; Sahni, Ramesh K.; Beňová, Kateřina; Liška, Julie (Frontiers in Nutrition, 2026)
Millet production has significantly increased to fulfill the nutritional needs of the increased population across the globe. Around the world, millions of people suffer from shortages of food and hunger. In the last few years, food supply has been influenced by many factors, such as changes in climate, increased population, and a slowing economy. Furthermore, many countries face undernutrition and overnutrition problems. Achieving nutritional and food security requires a transformative shift in the agricultural sector. Providing everyone with access to cheap, healthy, and affordable food as well as a nutritious diet is one way to reach our goal. The present study uses preferred reporting items for systematic review and meta-analyses (PRISM) to study the search strategy for recent advancements. Bioactive substances, minerals, and properties of cereal grains are impacted by various processing methods like parboiling, decoration, heating, soaking, germination, and fermentation. This paper aims to study the nutrient qualities and processing of antinutrient reduction methods, the nutritional composition of millets, their effects on consumption, and the nutritional characteristics of medicinal use. The highest dietary fiber content is in pearl millets (11.49%), followed by maize (10.20%). Millets contain carbohydrates, antioxidants, and biologically active compounds such as phenolic acids, carotenoids, flavonoids, minerals, and vitamins. The appropriate consumption of millets helps to reduce diseases like diabetes, cardiovascular diseases, inflammation, and malnutrition because of their low glycemic index, being gluten-free, and increased major nutrients. But overdose of millet consumption causes goitrogenic effects, kidney stones, thyroid dysfunction, allergic reactions, high sugar levels, and weight gain. Considering the modifications within millets’ nutritional value brought on by the process may benefit the food business, scientists, and consumers in choosing the best processing method to maximize nutrient content, boost nutrient bioavailability, and assist in promoting food and nutrition security.